Fe3O4@L‐lysine‐Pd(0) organic–inorganic hybrid: As a novel heterogeneous magnetic nanocatalyst for chemo and homoselective [2 + 3] cycloaddition synthesis of 5‐substituted 1H‐tetrazoles. (22nd December 2020) - Ashraf, Muhammad Aqeel; Liu, Zhenling; Li, Cheng; Zhang, Dangquan
Abstract : An efficient and sustainable synthetic protocol has been presented to synthesis and 5‐substituted 1H‐tetrazole privileged heterocyclic substructures. The synthetic protocol involves two‐component reaction between aryl nitriles and NaN3 in water using complex of L‐lysine‐palladium nanoparticles (NPs) modified Fe3 O4 nanoparticles as magnetically separable, recyclable, and reusable heterogeneous catalyst. Magnetically retrievable L‐lysine‐Pd(0) modified Fe3 O4 nanoparticles were applied in [2 + 3] cycloaddition synthesis of 5‐substituted 1H‐tetrazoles. The advantages of this strategy include easy recovery and efficient reusability of the expensive Pd NPs, obtaining high yields of [2 + 3] cycloaddition, short reaction times, and all of the reported synthetic strategies are being performed in water as green solvent for a wide range of substrates. Abstract : In this paper, we report that Fe3O4@L‐lysine‐Pd(0) catalyzed the direct synthesis of new 5‐substituted 1H‐tetrazoles derivatives via [2 + 3] cycloaddition reaction of various aryl nitriles with sodum azide in green media, which yielding a wide variety of new 5‐substituted 1H‐tetrazole derivatives in good to excellent yields and high purity.